Candida auris: A Comprehensive Review of an Evolving Pathogen and Strategies for Management - Bukhari, Saud; Al-Hejin, Ahmed; Al-Maaqar, Saleh; Alsubhi, Wael (Journal of Biological Insights, 2026)
The prevalence of human fungal infections is increasing rapidly, with Candida spp. being the most common cause of invasive infections. Candida auris, a new pathogenic yeast, has become a major nosocomial infection worldwide. It exhibits a distinct skin tropism and a lengthy half-life on human skin, leading to significant epidemics in healthcare settings. C. auris has acquired antifungal resistance, with some isolates exhibiting resistance to all three classes of antifungal medications. Recent findings of clinical isolates that are pan-resistant to azoles, echinocandins, and amphotericin B (AmB) highlight the serious and unresolved difficulties in treating infections linked to C. auris. Control has been hampered by the inability to identify using standard phenotypic and molecular methods, the unknown population prevalence, ambiguous environmental niches, and unexplained pathways of transmission. The growing use of preventive antifungal medications like fluconazole is believed to be a major contributing factor to the rising incidence of colonization and infection with non-albicans Candida species. C. auris has the potential to become a dominant opportunistic pathogen in critically ill patients due to its resistance.